The Effect of Youtube Video as Teaching Media on the Ability of Grade VII Students of SMP Negeri 8 Pematangsiantar in Writing a Recount Text - Karmila Sihombing; Bloner Sinurat; Leonita Maria Efipanias Manihuruk (The Future of Education Journal, 2024)
This research was carried out to find out the effect of YouTube Video on students’ ability in writing recount text at grade VII of SMP Negeri 8 Pematangsiantar which is conducted in two classes, namely the experimental class (VII-4) consisting of 30 students and control class (VII-3) consisting of 30 students. The writing test is used as the data collection instrument for the pre-test and post-test. The writing rubric score three elements: orientation, events and re-orientation. The experimental class mean score on the pre-test was 69,6 and the mean score of control class was 66,3. On the other hand, the mean of score in experimental class on post-test was 83,7, while the mean score of control class on post-test was 70,13. To acquire data, the researcher used test as instrument. The result of t-test was 8,023 which was higher than t-table at 5% of level significance (1,672). The result of significance value indicates that alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. It meant that there was significant effect by using YouTube Video at grade VII of SMP Negeri 8 Pematangsiantar in writing recount text.